Kebon Dalem 2 Elementary School Semarang Parenting Styles Based on Parents’ Educational Background (Journal of Primary Education, 2022)
Child development is strongly influenced by their family as the first environment and first source of education for the child. The purpose of this study is to provide an overview of parenting style based on parents’ educational background at SD Kebon Dalem 2. This study uses qualitative method with case study approach. The subject of this study are three pairs of parents of fourth grade students at SD Kebon Dalem 2. Data were collected through interviews, observations, and documentation method. The validity of the data was tested using the triangulation method. The result showed that parents with higher educational background (college graduates) and secondary educational background (junior and high school graduates) did not only apply one kind of parenting style. In terms of assisting academic and non-academic development, all parents apply democratic or authoritative parenting style. They supervise their children’s academic development at school, as well as provide support for their talents and interests outside of school. However, in terms of building independence, responsibility, and regulating the use of gadget, parents who are college and high school graduates apply authoritarian parenting style, resulting in their children being responsible and independent. On the contrary, parents with junior high school graduates apply permissive parenting style, resulting in the child being less responsible, less independent, and tend to use the gadget excessively. This research in expected to be able to provide inputs for parents, teachers, and school and to determine whether counseling is needed or not to improve student’s achievement.